The Analysis of Bahasa Indonesia Phrases in the Short Story Entitled "Balikui" by Putu Wijaya - Ekfindar Diliana; Halimah Anggun Nurrani; Marsela Wandawon; Veronika Dorotea Adongo Kaize; Dina Martha Jambormias; Katarina Tawurutubun (Musamus Journal of Language and Literature, 2023)
The work of literature cannot be separated from human life. They are like two sides of a coin; one of the literature words that really sticks to human life is short story. Short story belongs to one type of proses. The present study aims to analyze the type of prhase in the short story entitled ‘Balikui’ by Putu Wijaya. the research method used was a qualitative approach, because research is carried out by identifying, analyzing and describing the data. The results of this research show that the phrases were 18 prepositional phrases; 17 noun phrases; 28 verb phrases; 2 numeral phrases; 4 adverb phrases and 2 adjective phrases. Therefore, the short story texts have many different types of phrases. It is hoped that this research can add insight, especially to novice writers who are about to write a work. This is also an effort to minimize the presence of words that do not have complete meaning and unstructured sentences